Bail and remand for young people in Australia: a national research project - Kelly Richards
Abstract Funded and endorsed by the Australasian Juvenile Justice Administrators, this is one of the first national scale research reports into the bail and remand practices for young Australians. A young person can be placed in custody on remand (ie refused bail) after being arrested by police in relation to a suspected criminal offence, before entering a plea, while awaiting trial, during trial or awaiting sentence. Although custodial remand plays an important role in Western criminal justice systems, minimising the unnecessary use of remand is important given the obligations Australia has under several UN instruments to use, as a last resort, youth detention of any kind. This research identifies trends in the use of custodial remand and explores the factors that influence its use for young people nationally and in each of Australia’s jurisdictions